Clinical outcome and prognostic analysis of meningeal carcinomatosis treated by intrathecal chemotherapy. (4th July 2018) - Meng, Zhaohua; Zhang, Qinqin; Hong, Kun; Han, Weixin; Zhao, Zeyan; Liu, Yajuan; He, Junying; Bu, Hui
ABSTRACT: Objective : To evaluate the clinical efficacy of meningeal carcinomatosis (MC) treated by intrathecal chemotherapy (IC) and analyzes the prognostic factors. Methods : The clinical and follow-up data of 33 MC patients was collected and retrospectively analyzed. Potential prognostic factors such as age, gender, primary cancer, transfer time, presence of brain metastasis, intracranial pressure, protein, glucose, vascular endothelial growth factor (VEGF), eastern cooperative oncology group (ECOG) performance status (PS), systemic treatment and IC were discussed. Results : The most common clinical manifestation of MC was high intracranial pressure (30 cases). The negative rate of cerebrospinal fluid cytology was 50% after MC patients treated by IC. The remission rate of IC and no-IC group was 71.4% and 15.7%, respectively, of which the stability rate was 92.8% and 57.8% with significant difference. The median survival time was 5.200 months (95% CI 0.000–11.491) and the survival rate of 3, 6, 12 months were respectively 71.6%, 49.2%, 30.7%. Conclusion : IC can relieve the symptoms of MC and extend life expectancy. Early treatment can improve prognosis. Presence of brain metastasis, ECOG PS and IC were correlated with prognosis of patients, whereas IC is an independent prognostic factor.